2018
DOI: 10.1108/jsma-03-2018-0023
|View full text |Cite
|
Sign up to set email alerts
|

The role of cooperative alliances in internationalization strategy

Abstract: Purpose From the network approach, the purpose of this paper is to provide empirical evidence about the role of international cooperative alliances (CAs) in the decision of small- and medium-sized enterprises (SMEs) to internationalize and remain in the external market. Design/methodology/approach To fulfill the proposed objective, qualitative research was carried out through analyzing two SMEs (case studies) in the Portuguese textile sector. Data collection was based on structured interviews, direct observa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 81 publications
(130 reference statements)
0
2
0
Order By: Relevance
“…Thus, a highly built network relationship aids exporting entrepreneurs in gaining access to differentiated knowledge and distinctive resources which significantly increase market opportunities and competitive advantage and positively accelerate the pace, scope and degree of internationalisation (Barcelos et al , 2022; Santhosh, 2020). In the same vein, formal networking with an international agent and membership association is a source of information to enhance the international experience and competitiveness, to boost international activities (Boscor, 2015; Morais and Franco, 2018).…”
Section: Theoretical and Hypothesis Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, a highly built network relationship aids exporting entrepreneurs in gaining access to differentiated knowledge and distinctive resources which significantly increase market opportunities and competitive advantage and positively accelerate the pace, scope and degree of internationalisation (Barcelos et al , 2022; Santhosh, 2020). In the same vein, formal networking with an international agent and membership association is a source of information to enhance the international experience and competitiveness, to boost international activities (Boscor, 2015; Morais and Franco, 2018).…”
Section: Theoretical and Hypothesis Developmentmentioning
confidence: 99%
“…Moreover, it is acknowledged that social ties with members of the same ethnic group or national origins in the foreign country increase export activities (Santhosh, 2020). Firms assess their specific weaknesses and strengths and adopt a networking strategy, including formal and informal networking with families, friends, government executives, customers, suppliers, international agents or business partners which complement each other (Zain and Ng, 2006; Morais and Franco, 2018). Drawing from network theory (Casson, 1997; Casson, 2010), this study assessed the potential mediating roles of both formal and informal networks in the relationship between government support and the degree of internationalisation by indigenous Ghanaian firms.…”
Section: Introductionmentioning
confidence: 99%
“…However, this study also found that the networking program initiated by the government failed in its implementation. The research of Morais & Franco (2018) found that most of the internationalization processes in Portugal were initiated by MSMEs themselves and not by the existence of networks.…”
Section: Introductionmentioning
confidence: 99%